Learning strategies, an additional pinch to learning: A Study of the use of learning strategies by high school students in Mexico - Gutiérrez Sánchez, María Constanza Lidia; Martínez Pedraza, Laura (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This research presents an analysis of the learning strategies employed by students during confinement due to Covid-19 in the year 2021. The study sample consisted of 200 students from the Licenciado Benito Juárez García high school of the morning shift of the Benemérita Universidad Autónoma de Puebla. A survey was applied to measure the degree of satisfaction in relation to their use and impact on the acquisition of knowledge, allowing them to be more self-taught. The results show that the hypothesis was partially fulfilled, since practice and organization are the learning strategies that most supported them in learning.